State Obligations to Protect the Family in times of Peace and During Armed Conflicts - Ali, Assist. Prof. Dr. Haider Kazem Abd; Ali, Assist. Prof. Dr. Nasr Muhammad; Darwish, Dr. Majeed Majhoul (Journal of Legal and Political Studies, 2018)
This thesis highlights the important state’s obligations in family protection during peace time and during armed conflict, which enumerated in international treaties. The family protection subject occupies most prominent place in international conventions, agreements, charts and the constitutions states. While the protection of family rights is inevitable in peace times, it is most important during the armed conflict, consequently the human international law included many of obligations on the conflict parties in order to provide viable protection to family. this thesis divided into two parts; the first, deals with state obligation in family protection during peace times, while the second deals with family protection during armed conflicts.
Keywords: family protection; constitutions states; armed conflict; human international law